Kritik Hermeneutik Filsafat Islam atas Dominasi Positivisme dalam Pendidikan Madrasah di Indonesia - Purba, Ramauddin (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
Madrasah education in Indonesia, as an institution that combines Islamic values and science, now faces serious epistemological challenges due to the dominance of the positivist paradigm, which tends to reduce knowledge to empirical and measurable aspects. This dominance is not merely a methodological issue but also has a direct impact on the direction and quality of madrasah education, as it ignores the transcendental, metaphysical, and spiritual dimensions that are the core of Islamic epistemology. This study aims to specifically examine how a hermeneutic approach to Islamic philosophy can be used to reinterpret the relationship between revelation, reason, and educational reality, thereby offering a more comprehensive alternative paradigm. This study uses qualitative methods with a hermeneutic-philosophical analysis approach to classical and contemporary Islamic philosophical texts, as well as national education documents. The results show that positivism has been strengthened through evaluation standards based on cognitive achievement, the reduction of religious knowledge to an additional element, and the weak integration of spiritual values in learning practices. The hermeneutics of Islamic philosophy, with its emphasis on the dialogue between text, context, and subject, offers a path to epistemological reconstruction that affirms knowledge as a means to ultimate truth and strengthens the spiritual function of education. The conclusion of this study emphasizes the need for a reorientation of the madrasah education paradigm through the integration of Islamic epistemology, which not only strengthens students' spiritual character but also provides theoretical contributions in building an Islamic education model capable of transcending the hegemony of positivism.